2023
DOI: 10.3390/ani13040723
|View full text |Cite
|
Sign up to set email alerts
|

What Influences the Prevalence and Intensity of Haemoparasites and Ectoparasites in an Insular Lizard?

Abstract: Island biogeography theories predict that characteristics such as island size, age, and isolation interplay in host-parasite dynamics. In this study, we analyzed haemogregarines of the Aegean wall lizard, Podarcis erhardii, to investigate how island characteristics relate to parasite prevalence and intensity. A previous assessment of 19 Greek island populations suggested that isolation time and host population density were key predictors of haemogregarines. Here, by combining microscopy and genetic techniques,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Moreover, blood parasites native to the islands can be less virulent to insular hosts and, perhaps for this reason, highly abundant on some islands (García‐Ramírez et al., 2005; Garrido & Pérez‐Mellado, 2013; Magnanou & Morand, 2006; Megía‐Palma, Arregui, et al., 2020; Schall, 1986; Tomás et al., 2022). Recent research found that host density, island age, and vector prevalence are important predictors of blood parasite prevalence across insular populations of lizards (Ferreira et al., 2023; Fornberg & Semegen, 2021). High parasite prevalence might be explained by high transmission rates in highly dense host populations (Arakelyan et al., 2019; Buckley & Jetz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, blood parasites native to the islands can be less virulent to insular hosts and, perhaps for this reason, highly abundant on some islands (García‐Ramírez et al., 2005; Garrido & Pérez‐Mellado, 2013; Magnanou & Morand, 2006; Megía‐Palma, Arregui, et al., 2020; Schall, 1986; Tomás et al., 2022). Recent research found that host density, island age, and vector prevalence are important predictors of blood parasite prevalence across insular populations of lizards (Ferreira et al., 2023; Fornberg & Semegen, 2021). High parasite prevalence might be explained by high transmission rates in highly dense host populations (Arakelyan et al., 2019; Buckley & Jetz, 2007).…”
Section: Introductionmentioning
confidence: 99%